11β hydroxysteroid dehydrogenase type 1 transgenic mesenchymal stem cells attenuate inflammation in models of sepsis - Mahida, Rahul Y.; Yuan, Zhengqiang; Kolluri, Krishna K.; Scott, Aaron; Parekh, Dhruv; Hardy, Rowan S.; Matthay, Michael A.; Perkins, Gavin D.; Janes, Sam M.; Thickett, David R. (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Human bone marrow mesenchymal stem cell (MSC) administration reduces inflammation in pre-clinical models of sepsis and sepsis-related lung injury, however clinical efficacy in patients has not yet been demonstrated. We previously showed that Alveolar Macrophage (AM) 11β-hydroxysteroid dehydrogenase type-1 (HSD-1) autocrine signalling is impaired in critically ill sepsis patients, which promotes inflammatory injury. Administration of transgenic MSCs (tMSCs) which overexpress HSD-1 may enhance the anti-inflammatory effects of local glucocorticoids and be more effective at reducing inflammation in sepsis than cellular therapy alone.Methods: MSCs were transfected using a recombinant lentiviral vector containing the HSD-1 and GPF transgenes under the control of a tetracycline promoter. Thin layer chromatography assessed HSD-1 reductase activity in transgenic MSCs (tMSCs).. MSC phenotype was assessed by flow cytometry and bi-lineage differentiation. HSD-1 tMSCs were co-cultured with LPSstimulated monocyte-derived macrophages (MDMs) from healthy volunteers prior to assessment of pro-inflammatory cytokine release. HSD-1 tMSCs were administered intravenously to mice undergoing caecal ligation and puncture (CLP).Results: MSCs were transfected with an efficiency of 91.1%, and maintained an MSC phenotype. Functional HSD-1 activity was demonstrated in tMSCs, with predominant reductase cortisol activation (peak 8.23 pM/hour/100,000 cells). HSD-1 tMSC co-culture with LPS-stimulated monocyte-derived macrophages (MDMs) suppressed TNFα and IL-6 release.Administration of transgene activated HSD-1 tMSCs in a murine model of caecal ligation and puncture (CLP)CLP attenuated neutrophilic inflammation more effectively than transgene inactive tMSCs (medians 0.403 v 1.36 x10 6 /ml, p=0.033).The synergistic impact of HSD-1 transgene expression and MSC therapy attenuated neutrophilic inflammation in a mouse model of peritoneal sepsis more effectively than MSC therapy alone. Future studies investigating the anti-inflammatory capacity of HSD-1 tMSCs in models of sepsis-related direct lung injury and inflammatory diseases are required.